TESTING THE PURCHASING POWER PARITY THEORY: THE EXCHANGE RATES MOVEMENT IN KAZAKHSTAN. - Yerekenov, Chingiz (Nazarbayev University Graduate School of Business, 2023)
Purchasing Power Parity, or PPP, is an important concept that has several applications in economics and finance. According to Purchasing Power Parity theory, the exchange rates should adjust accordingly with the prices of similar goods in different countries to account for inflation. To put it in simpler terms, a certain basket of goods should be roughly of the same availability in terms of one currency, as well as in terms of another currency...
Keywords: type of access: gated access